Airborne Microbial Communities at High-Altitude and Suburban Sites in Toyama, Japan Suggest a New Perspective for Bioprospecting - Tanaka, Daisuke; Sato, Kei; Goto, Motoshi; Fujiyoshi, So; Maruyama, Fumito; Takato, Shunsuke; Shimada, Takamune; Sakatoku, Akihiro; Aoki, Kazuma; Nakamura, Shogo (Frontiers in Bioengineering and Biotechnology, 2019)
Airborne microorganisms, especially those at high altitude, are exposed to hostile conditions, including ultraviolet (UV) radiation, desiccation, and low temperatures. This study was conducted to compare the composition and abundance of airborne microorganisms at a high-altitude site, Mt. Jodo (2,839 m above mean sea level (AMSL)) and a suburban site (23 m AMSL) in Toyama, Japan. To our knowledge, this is the first study to investigate microbial communities in air samples collected simultaneously at two sites in relatively close proximity, from low and high altitude. Air samples were collected over a period of three years during 2009-2011. We then examined the bacterial and eukaryotic communities and estimated the abundance of bacteria and fungi with real-time TaqMan PCR. The airborne bacterial and eukaryotic communities differed between high-altitude and suburban sites on each sampling day. Backward trajectory analysis of air masses that arrived at high-altitude and suburban sites on each sampling day displayed almost the same paths. The bacterial communities were dominated by Actinobacteria, Firmicutes, and Proteobacteria, while the eukaryotic communities included Ascomycota, Basidiomycota, and Streptophyta. We also predicted some application of such microbial communities. The airborne bacterial and fungal abundance at the high-altitude site was about two times lower than that at the suburban site. These results showed that each airborne microbial communities have locality even if they are collected close location.